TeleSpeech Therapy Pilot Project: Stakeholder Satisfaction - Sena Crutchley; Michael Campbell (International Journal of Telerehabilitation)
This pilot study of a school-based telepractice pilot project in a rural, remote county of North Carolina investigated the satisfaction of parents/caregivers, teachers, and administrators with a year-long telespeech therapy program delivered by a university clinic. Upon completion of the almost year-long project, a satisfaction survey incorporating a 5-point equal-appearing Likert scale (1= strongly disagree; 5= strongly agree) was disseminated to the stakeholders.  The results sorted by the three populations surveyed, indicated stakeholder satisfaction with student progress toward their speech and language goals, and clinician accessibility and responsiveness (mean ratings > 4 points). The respondents (N=23) also indicated they would “recommend TeleSpeech Therapy to other school districts” (mean rating: 4.3).  The only mean rating below 4.0 was associated with teacher responses to the statement: “My expectations for the TeleSpeech Therapy program have been met” (mean rating: 3.92).   Overall, parents/caregivers, teachers, and administrators appeared to find telepractice a satisfactory service delivery model for school-based speech-language therapy.